Smog, Cognition and Real-World Decision Making - Xi Chen (Global Labor Organization (GLO), 2018)
Cognitive functioning is critical as in our daily life a host of real-world complex decisions in high-stakes markets have to be made. The decision-making process can be vulnerable to environmental stressors. Summarizing the growing economic and epidemiologic evidence linking air pollution, cognition performance and real-world decision making, we first illustrate key physiological and psychological pathways between air pollution and cognition. We then document the main patterns of air pollution affecting cognitive test performance by type of cognitive tests, gender, window of exposure, age profile, and educational attainment. We further extend to a review of real-world decision making that has been found to be affected by air pollution and the resulting cognitive impairments. Finally, rich implications on environmental health policies are drawn based on existing evaluations of social costs of air pollution.
Keywords: I24; Q53; Q51; G11; G41; J24; 330; Air Pollution; Cognitive Performance; Intelligence; Decision Making